SPECIAL ATTRIBUTIONS AND DEONTOLOGICAL RULES OF REGISTRARS’ PROFESSIONAL ACTIVITY REGARDING MARRIAGE AND DIVORCE - Ștefania Cristina Mirică; Andreea Elena Matic (Perspectives of Law and Public Administration, 2018)
The Registrar is a civil servant with special atributions regarding marriage and divorce. In Romania the registrars’ activity is established by Law no 119/1996 regarding the civil status documents with subsequent modifications and additions, Law no 189/1999 regarding the civil servant status with subsequent modifications and additions, the Civil Code, internal regulations of City Hall or Civil Status Service etc. In the present paper we aim to analyze the specific competences and deontological norms applicable to registrars in Romania on the occasion of marriage and the divorce by administrative procedure. If marriage procedure is an old, traditional attribution of registrars, its dissolution – the divorce through administrative procedure is a novelty as it has been recently established by our legislation. In our opinion the registrar’s activity regarding marriage and divorce has a special social importance due to the effects and implications of these events in the lives of the beneficiaries. There for, we consider that the main aspects of these attributions include not only the verification of the procedure and of the supporting documents submitted, but also the communication of the values and respect for family life to the persons involved.